Answer:
The three roots of the equation are, x = +9 , x = -9 and x = 2
Explanation:
Data given in the question:
(x² − 9)(x³ − 8) = 0.
Now,
for the above relation to be true the following condition must be followed:
Either (x² − 9) = 0 ............(1)
or
(x³ − 8) = 0 ..........(2)
Therefore,
considering the equation 1, we have
(x² − 9) = 0
adding 9 to the both sides
we get
x² − 9 + 9 = 0 + 9
or
x² + 0 = 9
taking the square root both the sides, we get
√x² = √9
or
x = ± 9
thus,
x = + 9 and, x = -9
considering the equation 2, we have
(x³ − 8) = 0
adding 8 both the sides
we have
x³ − 8 + 8 = 0 + 8
or
x³ = 8
or
x³ = 2 × 2 × 2
taking the cube root both the sides, we get
∛x³ = ∛(2 × 2 × 2)
or
x = 2
Hence,
The three roots of the equation are, x = +9 , x = -9 and x = 2